Obravnava bolnika z motnjo, vezano na uživanje psihoaktivnih snovi, in komorbidno psihotično motnjo - Šegrec, Nuša (Zdravniški vestnik, 2010)
The term dual diagnosis is used to describe the comorbid condition of substance use disorder and other mental disorder. The prevalence of substance use disorders is higher among patients with other mental disorders than in general population. Regarding prognosis in the treatment of patients with comorbid disorders, both disorders have a poorer outcome when undertreated. There are four models explaining aetiology of dual diagnosis: common factor models, secondary substance use disorder models, secondary psychiatric disorder models and bidirectional models. Differentiation between primary psychotic disorders that co-occur with substance use and substance induced psychosis is generally difficult, but it is important for understanding the course of illness and effective treatment planning. Three treatment approachesare used in patients with comorbid substance use disorder and another mental disorder: parallel, sequentional and integrative - the last onesupposed to be more effective than others. Therapeutic approaches in the treatment of patients with dual diagnosis include psychoeducation, motivational interventions, cognitive-behavioural therapy, social skills training and psycho-pharmacotherapy.
Keywords: Comorbidity; Diagnosis; diagnostika; droge; duševne motnje; odvisniki; Psihotropna zdravila; Psihoze; Psychotic Disorders; Psychotropic Drugs; Soobolevnost; Substance Abuse; Therapy; zdravljenje